Agelanius burgeri, a new species of horse fly from south Chile (Diptera: Tabanidae) - González, Christian R. (Zootaxa, 2006)
The female and male of Agelanius burgeri, new species, from Nueva Imperial, Cautín Province, Chile are described and illustrated. Its relationship to other Agelanius species is discussed.